The Role of Islamic Philanthropy Institutions in Realizing the 5th core on Pancasila : The role of LAZISMU in realizing the values of social justice - Farhan, Muhamad (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
Pancasila is our philosophy and guideline in nation and state. In realizing the values ​​of Pancasila, it is very difficult because this nation is very large. Therefore, the State really needs help from civil society. Philanthropy is an activity to do good or give charity to others so as to bring prosperity to the community. A philanthropic activity is needed to flatten the welfare of the people. This paper contains the actions of one of the Islamic Philanthropy institutions namely Lazismu in combating poverty evenly throughout Indonesia. Lazismu is an Islamic Philanthropy organization under the auspices of Muhammadiyah. The institution is helping the government to realize social welfare as mandated by Pancasila. This paper uses qualitative methods and descriptive analysis. Lazismu's role in the distribution of people's welfare in its strategic programs is very helpful for the government. As a result, the Government and Lazismu along with other social movements can ground Pancasila values ​​in Indonesia, especially the 5th principle.